ANALYSIS OF CONSUMER PERCEPTIONS IN POSITIONING FROZEN FOOD PRODUCTS IN PEKANBARU CITY - Fadilah, Nurul; Jushermi, Jushermi; Musfar, T. Firli Musfar (Cahaya Ilmu Bangsa, 2024)
The frozen food market in Pekanbaru, Indonesia, has experienced notable growth, particularly in the wake of the Covid-19 pandemic, influenced by shifts in consumer lifestyles and a growing preference for convenience. This study employs Multi-Dimensional Scaling (MDS) techniques to analyze consumer perceptions of frozen food products, effectively mapping preferences and expectations. The MDS outcomes illustrate that the x-axis indicates consumer preference for frozen foods, with proximity to the origin denoting higher preference levels, while the y-axis represents consumer expectations. Findings reveal a strong consumer demand for broader access to frozen food, highlighting packaging as a critical area for improvement. Additionally, perceptions indicate that frozen foods are often regarded as inferior to fresh alternatives, attributed to concerns surrounding preservatives and health. The analysis identifies sausages, meatballs, and French fries as preferred products, in contrast to nuggets, which received lower consumer favor. These insights underscore the significance of accessibility, packaging, and product presentation in enhancing consumer engagement and satisfaction within the frozen food sector.